(untitled) (Research, Society and Development, 2025)
Pressure injuries are damage to the skin or soft tissues caused by intense and prolonged pressure or by medical devices. These injuries may occur due to surgical positioning, which aims to ensure adequate access to the operative field. This study aimed to assess the prevalence of pressure injuries related to surgical positioning and to identify associations between care and patient profile characteristics and the development of such injuries. A descriptive, observational, cross-sectional, and quantitative study was conducted with 81 patients. A sociodemographic questionnaire, the ELPO scale, and a physical examination were applied to evaluate the development of pressure injuries. Data were analyzed using descriptive statistics and the chi-square test (p < 0.005). A prevalence of 56% of pressure injuries was observed. Age (p = 0.003), white skin color (p = 0.0003), diabetes mellitus (p = 0.003), and ELPO classification as high risk (p = 0.000) were associated with the occurrence of injuries. These findings highlight the importance of adopting appropriate preventive measures in the surgical setting to avoid the occurrence of this adverse event.